Trichoderma spp. from Misiones, Argentina: effective fungi to promote plant growth of the regional crop Ilex paraguariensis St. Hil - López, Ana Clara (2019)
Ilex paraguariensis St. Hil (yerba mate) is an important crop in the north of Argentina, mainly in Misiones province. The application of Trichoderma as a biocontroller and biofertilizer can replace or reduce the use of agrochemicals, decreasing the negative ecological impact. In this research, we evaluated in vitro and in vivo antagonistic and plant growth promoting (PGP) properties of Trichoderma species isolated from different regions of Misiones province. Dual culture assays of Trichoderma against phytopathogenic fungi associated with yerba mate showed that T. stilbohypoxyli LBM 120 was the most effective antagonist, inhibiting in more than 75% all phytopathogen growth. Trichoderma atroviride LBM 112 and T. stilbohypoxyli LBM 120 were positive on endoglucanase, protease, chitinase, siderophore production, and phosphate solubilisation showed the best biological control agents and PGP properties. The PGP properties of Trichoderma spp. evaluated in vivo on yerba mate seedlings showed that T. atroviride LBM 112, T. stilbohypoxyli LBM 120, and T. koningiopsis LBM 219 enhanced plant dry weight over 47% in total and 24% in the aerial part. Moreover, T. koningiopsis LBM 219 increased root dry weight 25% in contrast with in vitro controls. In conclusion, native Trichoderma strains could be a sustainable solution to improve yerba mate yield.